Characteristics of progressive temporal visual field defects in patients with myopia - Jiyun Lee (Nature Portfolio, 2021)
Abstract Temporal visual field damage (VFD) is the common type of non-glaucomatous VF defects found in eyes with myopia. However, little is known about the factors associated with its progression. We investigated the characteristic of myopic eyes with progressive temporal VF defects. This retrospective, observational study included a total of 116 eyes: 39 eyes with temporal VFDs and an axial length greater than 24.5 mm, 77 eyes with typical glaucomatous VFDs who were followed up more than 5 years. VF progression was evaluated with Trend-based global progression analysis. In the temporal VFD group, the greater tilt ratios, the higher prevalence of β-zone peripapillary atrophy (β-PPA), the substantial increase in β-PPA were found, compared to the typical glaucomatous VFD groups (all P-values ≤ 0.001). The temporal VFD group had the slower progression than the typical glaucomatous VFD group on trend-based GPA (P = 0.047). In the multivariate linear regression analysis, the change of β-PPA area over years was related to temporal VFD progression (B, − 0.000088, P = 0.003). In conclusion, myopic eyes with the temporal VFD, which come with growing β-PPA area, should be monitored with extra caution.